Perspective: Systems biology beyond biology - Voit, Eberhard O. (Frontiers in Systems Biology, 2022)
The past decades have witnessed an astounding rise of the nascent field of systems biology. By and large unknown and ignored for a long time, the field rapidly moved into the limelight and is now in the process of becoming a widely recognized and respected component of mainstream biology. Of course, much remains to be explored and accomplished in systems biology within its parent domain of biology, but the time seems ripe for expansions beyond this domain. The goal of such an expansion should not be the creation of new strongholds or academic silos outside biology, but the true integration of biological systems thinking into educational programs of other disciplines. The expansion should naturally start with closely related fields like biophysics, biochemistry, bioinformatics, and bioengineering, but should continue further into other areas invested in the study of life, such as medicine, epidemiology, and public health, as well as applied mathematics and computer science. This perspective sketches out how systems biology might be able to enrich the training of a new generation of scientists in these fields of scientific endeavor.